An Analytical Look at the History of the Art of Uzbek Folk Instruments - Marifatkhon, Khuraliyeva (International Journal on Orange Technologies, 2023)
this article looks at the appearance of Uzbek folk instruments that appeared in the distant past and their origin. According to the data, it is assumed that the first musical instruments were created in 13 thousand years BC. We analyzed that the appearance of the first percussion instruments and ancient labor songs are directly related to the rhythmic structure of work.